Decoding Cyber Law: Insights from Longitudinal Comparisons - Romadhon, Fajar Riski; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article investigates 10,446 journal articles from the Lens.org database, focusing on Cyber Law and Longitudinal Comparison. It aims to uncover multifaceted dimensions of cybercrime and its legal implications. Examining challenges in explaining cyber offenses from a criminological standpoint, it delves into the intersection of cyberfraud with international law enforcement. Additionally, the study explores how employment and financial support impact criminal behavior. Notably, it highlights the significance of peer associations, norm acceptance, and adolescent violent delinquency. The findings offer a valuable resource, providing unique insights into cyber-related criminal activities, essential for global academics, policymakers, and researchers.Highlights : Multifaceted Exploration: Investigates various aspects of cybercrime and its legal implications. Intersection of Cyberfraud and Enforcement: Explores the relationship between cyberfraud and international law enforcement efforts. Social Influences on Criminal Behavior: Highlights the impact of peer associations, norms, and adolescent delinquency on cyber-related crimes. Keywords: Cyber Law, Longitudinal Comparison, Criminological Explanations, International Law Enforcement, Criminal Behavior Influences